A Worldwide Map of Human Structural Variants. Issue 10 (October 2020) - Montinaro, Francesco; Capelli, Cristian
Abstract : Genomic variation extends from single nucleotide variants to large chromosomal rearrangements, but the extent of structural variation in Homo sapiens is still unclear. Almarri et al. provide a worldwide catalogue of structural variants present in human populations. Most of the reported variation is novel, with some variants being inherited from Neanderthals and Denisovans. Drift and selection shaped the distribution of these variants with some suggested to have functional implications.